Die Privatisierung der öffentlichen Arbeitsvermittlung: Erfahrungen aus Australien, den Niederlanden und Großbritannien - Oliver Bruttel (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2005)
– This article examines the consequences of contracting-out on the basis of the four criteria of efficiency, economy, effectiveness and equality (3 or 4 e's concept), which are borrowed from New Public Management research. The paper is based on 76 expert interviews and informative discussions conducted in the three countries. In addition, contractual documents and other primary sources were evaluated and the existing secondary literature was taken into account. To sum up, private providers seem to have advantages in all four dimensions. Efficiency can be increased by competition incentives, outcome-dependent payment and a sustained measurement of performance. It is possible to achieve a higher level of economy by means of modern personnel policy and the scope available to private providers in buying in additional expertise for their case management. The effectiveness of job placement is raised in particular by the flexibility of the providers. The danger of private providers taking the pick of the bunch can be counteracted, perhaps even better than in a public employment service, by various mechanisms (e.g. performance measurement, differentiation of target groups or involvement of the job-seekers in the quality control). The increasing distribution of contracting-out in countries other than those observed here (e.g. Belgium, Denmark) should be a reason to lead an open discussion about this reform approach in Germany too.
Keywords: 330; Arbeitsvermittlung; Privatisierung - internationaler Vergleich; private Arbeitsvermittlung; Wirtschaftlichkeit; Gerechtigkeit; institutionelle Faktoren; Transaktionskosten; Produktionskosten; Kompetenzverteilung; Arbeitsverwaltung; private Arbeitsvermittlung - Effizienz; Australien; Niederlande; Großbritannien